Features of carrying out of physical rehabilitation at patients on bronchial pneumonia. - Grygus I.M; Mironyuk L.V (Kharkov National Pedagogical University, 2011)
Purpose - to study influence of the offered program of physical rehabilitation on the state of patients pneumonia. In the article the features of leadthrough of physical rehabilitation are examined for patients by bronchial pneumonia in a hospital period. Basis of the offered program was included by medical physical culture and massotherapy. Application of the worked out program of physical rehabilitation on a background medicinal treatment the improvement of feel, general, proceeding in a capacity allowed quicker to mark, the symptoms of illness disappeared before, the indexes of function of the external breathing, auscultative data of lungs, got better.